English Day: A Significant Pedagogical Experience (2023)
This document aims to show the systematization of a pedagogical experience that arises from the planning and execution of the English Day at Ciudad de Bogotá school in the afternoon shift during the pandemic, allowing the teacher to make a reflective analysis of their work in order to improve their pedagogical practices in a virtual way and the student demonstrate their skills in a second language through a specific and real context.